An Anticolonial Framework for Urban Teacher Preparation. Issue 3 (3rd July 2018) - Lyiscott, Jamila J.; Caraballo, Limarys; Morrell, Ernest
ABSTRACT: Our contemporary apprenticeship model of teacher education often places preservice teachers in learning environments where they never witness the types of dynamic and engaged practice they desire to emulate. Either there are structural limits within the classroom placed by school or district leadership or there are preselected veteran mentor teachers who do not value the same kinds of critical practice. These challenges necessitate a radical rethinking of how and where preservice teachers learn their craft. We pose an anticolonial model of teacher development, one that situates teachers and students in collaborative networks where they work powerfully together via Youth Participatory Action Research on projects that have significant social, cultural, and digital relevance. The purposes of this article are (a) to propose the essentiality of anticolonial approaches to reimagine the preparation of preservice teachers and (b) to demonstrate how these approaches are enacted in our own practice within critical, project-based clinical experiences with preservice educators toward the development of an anticolonial model for urban teacher preparation.